The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1177/004947559802800111
|View full text |Cite
|
Sign up to set email alerts
|

Giardiasis in the Adult Population of Dakshina Kannada District of South India

Abstract: A 10-year study of Giardia intestinalis infections in adults was conducted in the Dakshina Kannada District of Karnataka State, South India. Coproparasitological investigations were made on 10,000 stool specimens collected from selected patients. The infection rate was 37.1% with a male disease rate of 91.4%. The highest incidence rate was recorded in the age group 15-26 years. A possible reason for this preponderance of giardiasis in these males, is discussed. The optimum time for transmission appeared to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…32 Seasonal variation in prevalence has also been reported in developed and developing countries in temperate and tropical regions. [33][34][35][36][37] Diarrhoea/loose motions, abdominal discomfort/pain in abdomen and anemia were some of the most common clinical symptoms of subjects enrolled in the study. These are some of the commonly associated symptoms with infectious intestinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…32 Seasonal variation in prevalence has also been reported in developed and developing countries in temperate and tropical regions. [33][34][35][36][37] Diarrhoea/loose motions, abdominal discomfort/pain in abdomen and anemia were some of the most common clinical symptoms of subjects enrolled in the study. These are some of the commonly associated symptoms with infectious intestinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have found a similar correlation in Nicaragua, the Pacific Islands, the Philippines, and Thailand [5][6][7][8]. More specifically, heavy rainfall has been implicated in increased transmission of Giardiasis in the adult population of Dakshina Kannadad district of south India (9), cholera in Indonesia [9,10] and the Philippines, and Shigella in Thailand [7,11].…”
Section: Discussionmentioning
confidence: 67%
“…No correlation was found in studies in southern Brazil, Varanasi, India, or Malaysia [9,12,13]. In fact, the human rotavirus diarrheal cases in Kuwait and Dibrugarh, India decreased during the rainy season [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Figures 1 and 2 which indicates that the two parasites Entamoeba histolytica and Giardia lamblia have their common source of infection that is contaminated water and contaminated food. Other researchers have also reported the different infestation in their studies referring to similar factors (Sharma et al, 2004)while many studies have also mentioned that the males have a more incidence of these parasites (Shenoy et al, 1998) and this may be because the males have more outdoor actions if compare to females in rural areas in addition that they are more exposed to unhealthy ecological situations (Sayyari et al, 2005) .…”
Section: Resultsmentioning
confidence: 91%